Strategi Industrialisasi: Analisis Struktur Industri Unggulan Pada Pembangunan Negara - Shinta Rahma Diana; Muhammad yasin (Jurnal Relasi Publik, 2024)
Economic development is one of the key aspects in achieving societal prosperity and overall country growth. In an effort to achieve this goal, many countries adopted industrialization strategies as a foundation for their economic development. This strategy emphasizes the development of the industrial sector as a motor of growth that can move the economy in a stronger and more sustainable direction. However, it needs to be understood that the process of implementing an industrialization strategy is not easy, and often involves various challenges and risks that need to be overcome.